Skellig - Almond, David 1951- (New York Dell Yearling, 1998)
Unhappy about his baby sister's illness and the chaos of moving into a dilapidated old house, Michael retreats to the garage and finds a mysterious stranger who is something like a bird and something like an angel.
Prequel: My name is Mina.
"First published in Great Britain"--verso
Michael L. Printz Award for Excellence in Young Adult Literature
Keywords: Strangers -- Fiction; Angels -- Fiction; Moving, Household -- Fiction; Families -- Fiction. -- England; England -- Fiction